2022
DOI: 10.1039/d1nr06029e
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-treated TiO2 shows improved alcohol dehydration activity and selectivity

Abstract: The dehydration of alcohols is an important class of reactions for the development of fossil-free fuel and chemical industries. Acid catalysts are well known to enhance reactivity of alcohols following...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…Sulfur is present in the nanocasted samples as a byproduct of the use of dimethyl sulfoxide solvent during the POF synthesis that breaks down into sulfur-containing species that adsorb on the alumina and ceria surfaces. 60 The profile for SO 2 release matches published results for thermal decomposition of cerium sulfate. 61 Ceria that is exposed to sulfur is known to readily form cerium sulfate, and cerium sulfate has been shown to increase support acidity.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Sulfur is present in the nanocasted samples as a byproduct of the use of dimethyl sulfoxide solvent during the POF synthesis that breaks down into sulfur-containing species that adsorb on the alumina and ceria surfaces. 60 The profile for SO 2 release matches published results for thermal decomposition of cerium sulfate. 61 Ceria that is exposed to sulfur is known to readily form cerium sulfate, and cerium sulfate has been shown to increase support acidity.…”
Section: ■ Results and Discussionsupporting
confidence: 80%
“…A temperature-programmed steam treatment experiment revealed that SO 2 was released at 800 °C (Figure S32). Sulfur is present in the nanocasted samples as a byproduct of the use of dimethyl sulfoxide solvent during the POF synthesis that breaks down into sulfur-containing species that adsorb on the alumina and ceria surfaces . The profile for SO 2 release matches published results for thermal decomposition of cerium sulfate .…”
Section: Results and Discussionsupporting
confidence: 70%